Distorted monopolistic competition - Kristian Behrens; Giordano Mion; Yasusada Murata; Jens Suedekum (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
We characterize the equilibrium and optimal resource allocations in a general equilibrium model of monopolistic competition with multiple asymmetric sectors and heterogeneous firms. We first derive general results for additively separable preferences and general productivity distributions, and then analyze specific examples that allow for closed-form solutions and a simple quantification procedure. Using data for France and the United Kingdom, we find that the aggregate welfare distortion due to inefficient labor allocation and firm entry between sectors and inefficient selection and output within sectors is equivalent to the contribution of 68% of the total labor input.
Keywords: D43; D50; L13; 330; monopolistic competition; welfare distortion; intersectoral distortions; intrasectoral distortions